ELEMENTARY SCHOOL TEACHERS’ PERCEPTION ON INCLUSIVE EDUCATION IN BIREUEN DISTRICT - Fajrinur Fajrinur (FKIP, 2021)
The purpose of this research is to determine elementary schools teachers’ perception on inclusive teaching in Bireuen as well as to investigate whether or not teachers from inclusive school and teachers from non-inclusive schools show significant differences in term of perception. The participants of this research were two teachers from inclusive school and another two from non-inclusive schools. They were selected based on their willingness to involve in the research. This research was qualitative study so interview guide were used to collect data. The collected data were analysed and interpreted through qualitative procedures; data condensation, data display and data verification. The results of the interview show that teachers have positive outlook toward inclusive education. The non-inclusive teachers are on the right tract of becoming better inclusive teachers. There were no significant differences in perception about inclusive education between non-inclusive teachers and inclusive teachers. What differentiates them is their self-efficacy. Keywords: Inclusive education, perception, special needs